The impact of local climate data (temperature and wind) on urban design - Sulaymaniyah city as a model - عباس, ارام داود (Sulaimani Journal for Humanities, 2019)
The impact of local climate data in the city of Sulaymaniyah is direct and effective especially the sun, heat and direction of the wind on the design of the modern residential unit. The climate affects the nature of life inside and outside the house, which requires concerning several effective parameters in the field of architecture and design, especially that the radiation budget for the city of Sulaymaniyah is positive and where the average value of radiation gained during (1990 - 2015) (72.55 kW / m2) Peak in the summer seasons with increased length of day, where the amount of radiation received in the summer (22.24 kW/ m2 / day). This large quantity of heat needs energy to soften the atmosphere within the residential unit, and the engineering designer has to concern such power saving in the modern design of the housing unit taking into account the local climate conditions of the city. There is also a relationship between the wind and the direction of the residential unit and the proportion of openings and spaces and divisions of services of the house, especially that the wind speed in some days up to (15 m/s), which affect the choice of sites services house (kitchen and bathrooms). In order to avoid the unpleasant odors and fungi inside the house, Designer should observe the flow of wind within the residential unit.